PENGARUH LEVERAGE OPERASI DAN MAKROEKONOMI TERHADAP RETURN SAHAM DI JAKARTA ISLAMIC INDEX (JII) - Kartika Sekar Anggraini (2020)
This research was conducted to see the effect of operating leverage, inflation, and interest rates on stock returns. Where the object of research is 14 companies on the Jakarta Islamic Index (JII) stock index during 2015-2019 using purposive sampling data collection techniques. By using panel data regression analysis that combines cross section data and time series, the Common Effect Model was chosen as the model used in this study. Where the results obtained by using the Eviews8 statistical program states that operating leverage has a positive effect on Stock Returns while interest rates have a negative effect and on stock returns. Inflation has no effect on stock returns.